PENGARUH PENGETAHUAN EKONOMI DAN PENDAPATAN TERHADAP KONSUMSI MAHASISWA - Fikri, Khusnul; Sudrajat, Usep (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research is conducted at Sekolah Tinggi Ilmu Enkonomi Indragiri (STIE-I) Rengat. The formulation of the problem is whether economic knowledge and income simultaneously and partiallyÂ  effect on the student consumption. This research is to find out and analyze of the economic knowledge and income simultaneously and partially effect on teh student consumption. In this research, the sampling uses Slovin Formula method, with 81 respondents. Respondents in this research are active students on the fourth semester, 2018/2019. The analytical tool applies Multiple Linear Regression Analysis with a quantitative descriptive analysis approach and SPSS Version 21 Software. The research results can be concluded that: (1) Knowledge of economy and income together (simultaneous) have a significant effect on consumption. (2) Partial economic knowledge has no significant effect on consumption. (3) Revenues partially have a significant effect on consumption. (4) The determination coefficient of 0.178 means that the consumption variable can be explained by the variable knowledge of economy and income of 17.8%, while the remaining 82.2% is explained by other independent variables not examined in this research